Changes of Foetal Fluid Volume and Colour during Different Stages of Pregnancy in Sheep - KHATUN, A; WANI, G M; CHOUDHURY, A R; KHAN, M Z (The Indian Journal of Animal Reproduction, 2023)
The study consisted of eighty six samples of gravid and non-gravid uteri from the different local slaughter houses. The gravid uteri of sheep ranging from 14 to 140 days of gestation were divided into five groups e.g. Group A (GpA), Range: 14 - 57 days and Mean± S.E : 41 .40 ± 2.17; Group B (GpB), Range: 58 -74 and Mean± S.E: 67.87 ± 1.38; Group C (GpC), Range: 75 - 93 and Mean± S.E: 89.20 ± 2.33, Group D (GpD), Range: 94 - 120 and Mean± S.E: 110.60 ± 3.14 and Group E (GpE), Range:121 - 140 and Mean ± S.E : 130.0 ± 2. 79. Subsequently, GpA which is related to early pregnancy was subdivided into five groups viz. Group A1 (GpA 1). Range: 14 - 39 days and Mean ± S.E: 27.5 ± 2.70; Group A2 (GpA2). Range: 40-44 days and Mean± S.E: 42.16± 0. 75; Group A3 (GpA3) , Range: 45-48 days and Mean ± S.E: 46.8 ± 0.58; Group A4 (GpA4). Range: 49-52 days and Mean ± S.E: 51.4 ± 0.51 and Group As (GpA5). Range: 53-57 days and Mean± S.E: 55.75 ± 0.63. The mean foetal fluid volume in amniotic and allantoic fluid from GpA to GpE was 62.77 ± 13.13, 259.75 ± 14.16, 290.00 ± 14.72, 374.00 ± IO.SO, 200.00 ± 17.91 and 54.62 ± 8.78, 133.75 ± 16.76, 191.25 ± 5.56, 314.25 ± 1.93, 523.75 ± 41.99, respectively. The mean foetal fluid volumes for amniotic and allantoic fluids from GpA1 to GpA5 was 1.37 ±0.23, 11.88±3.11,61.80± II.II, 133.50±6.13, 148.70±0.51 and 12.87±3.25,37.82±3.60,53.23± 1.94, I 09.50 ± 10.17, 126.50 ± 1.55, respectively. Although the volume of allantoic fluid increased with higher gestation period, however, the amniotic fluid decreased during the terminal stage of gestation. There was change of colour and consistency of foetal fluids from transparent white to yellow, granular and viscous with higher gestational age.